162 Optimising the clinical pathway for placental histology. (16th November 2020) - Din, Nazia; Gentles, Nicole; Allison, Benjamin; Hickland, Maria; Lloyd, Jilly; Jakes, Adam D
Abstract : The Royal College of Pathologists (RCPATH) sets criteria for requesting placental histological examination which allows identification of pathological processes contributing to/causing an adverse obstetric outcome. Maternal intrapartum pyrexia is an essential criterion but is not part of the Guy's and St. Thomas' Trust (GSTT) guideline. There is no current baseline data on this at GSTT. Aim: To review current practice of requesting placental histology and amend trust guidelines to follow national recommendations. Birth records from June 2019 were reviewed showing 8%(47/569) of deliveries were eligible for placental histology as per trust criteria but only 60%(28/47) were requested. A survey demonstrated 4% of staff were able to correctly identify all criteria for histology and there was confusion regarding formalin use. Neonatologists and pathologists were contacted to identify views on the usefulness of placental histology and the effect of adopting national criteria. The pathologists confirmed all placentas should be sent in formalin unless specified by the obstetric team. The intrapartum infection guideline was amended to include requesting placental histology after approval by the intrapartum committee. The obstetric theatre posters were amended to include the extended criteria. A training presentation was emailed to all staff on the procedure for requesting placental histology. The trust guidelines were successfully amended to include RCPATH criteria for placenta histology. Birth records from January 2020 identified 13%(63/487) of deliveries were eligible for placental histology, but only 56%(35/63) were requested. The trust guideline for requesting placental histology now follows national recommendations. This may provide answers for adverse obstetric outcomes and reduce trust medicolegal costs. Unfortunately, no improvement in placental histology requests was demonstrated. Exploring potential barriers to improvement will be part of the next change cycle.